Descriptive and factor analysis of the Developmental Coordination Disorder Questionnaire (DCDQ'07) in a population‐based sample of children with and without Developmental Coordination Disorder. Issue 1 (29th August 2012) - Rivard, L.; Missiuna, C.; McCauley, D.; Cairney, J.
Abstract Background The Developmental Coordination Disorder Questionnaire (DCDQ'07) discriminates children with Developmental Coordination Disorder (DCD) from their peers. Studies employing the DCDQ have typically used clinical samples. To further validate the DCDQ'07, this study: (1) described its distributions in a population‐based sample, and a sample of children with DCD; (2) explored sex and age differences at important cut‐points; and (3) examined its factor structure. Methods This secondary analysis of data collected from 23 schools (n = 3151) included a sample of 3070 children (1526 boys, 1544 girls) and a sample of 122 children (73 boys, 49 girls) who met DCD diagnostic criteria. DCDQ'07 distributions were described by age and sex. Chi‐square analyses were conducted using three clinically important percentile ranges; a factor analysis explored the construct validity of DCDQ scores. Results Parents of 3070 children (97.4%) completed the questionnaire independently. Significant sex differences were noted in both samples. Significant differences in proportions by sex, and DCDQ means by age were found in the population sample. A three‐factor solution was found, accounting for 70.3% of the variance. Conclusions This is one of the largest studies using the DCDQ'07 with a non‐clinical sample. The three‐factor solution, including item loading, was consistent with previous research. When using DCDQ cut‐offs it is important to consider sex and age.